Integrating Geodetic Infrastructures for Gnss Displacements Analysis in Chile: A Case Study with Redgeomin (2019–2022) - Caverlotti-Silva, M; Tarrio-Mosquera, J (KeAi Communications Co., 2025)
This article investigates crustal displacements in Chile between 2019 and 2022, a region marked by the interaction between three Plates. Utilizing the Red Geodésica para la Minería (Geodetic Network for Mining, REDGEOMIN), which incorporates GNSS stations within Chile and fiduciary stations from the International GNSS Service (IGS) and the Sistema de Referencia Geodésico para las Américas (Geodetic Reference System for the Americas, SIRGAS) outside the country, our solutions are aligned with the International Terrestrial Reference Frame (ITRF). This approach ensures our research has significant local relevance and contributes to the global scientific community. This work thoroughly analyses GNSS geodetic infrastructure and covers equipment specifications, post-processing data availability, and quality control measures. REDGEOMIN s methodology aligns with IGb14 and the SIRGAS-Continuously Operating Network (SIRGAS-CON), ensuring precision and reliability. The primary objective of this research is to identify regions with significant displacement and areas requiring densification to improve vector variation. The study achieved high precision in aligning station coordinates to the IGb14 frame, with deviations of less than 1 mm, and to SIRGAS-CON, with deviations of 1 mm in planimetry and 2 mm in altimetry. The temporal evolution from 2019 to 2022, analyzed through the Analysis Deformation Beyond Los Andes (ADELA) project, reveals 3–5 cm/year displacements during interseismic periods, with contrasting directions in the northern and south-central regions. Metric displacements during co-seismic periods underscore the compelling necessity for kinematic reference frames in Chile and the incorporation of co-seismic displacement into scientific processing software. Therefore, this study ultimately emphasizes the need to establish a robust geodetic infrastructure in Chile, aiming for a comprehensive characterization and monitoring of the existing geodynamic processes in this region. These results, with their significant practical applications for future geodetic research and mining in Chile and internationally, enhance the precision and safety of mining operations in seismic zones, thereby demonstrating the relevance and applicability of the findings. © 2024 Editorial office of Geodesy and Geodynamics